Sociology - Schaefer, Richard T.; Lamm, Robert P. (New York : McGraw-Hill, 1983)
"Sociology is divided into five parts which provide a systematic introduction to the study of human behavior. Part one focuses on sociological theories and research methods. In part two, students learn how social life is organized. The basic sociological concepts of culture, society, social structure and socialization are defined and explored. Careful attention has been given to presenting understandable and accurate definitions of each key term. Each chapter contains a brief summary to aid the students in reviewing the important themes of the textbook. An annotated list of additional readings concludes each chapter."
Includes bibliographical references.
English note.
Keywords: Sociology; United States -- Social policy